The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/0004-6361/201526244
|View full text |Cite
|
Sign up to set email alerts
|

Carbon gas in SMC low-metallicity star-forming regions

Abstract: This paper presents [C II], [C I] and CO emission line maps of the star-forming regions N 66, N 25+N 26, and N 88 in the metalpoor Local Group dwarf galaxy SMC. The spatial and velocity structure of the large H II region N 66 reveals an expanding ring of shocked molecular gas centered on the exciting star cluster NGC 346, whereas a more distant dense molecular cloud is being eroded by UV radiation from the same cluster. In the N 25+N 26 and N 88 maps, diffuse [C II] emission at a relatively low surface bright… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 52 publications
7
27
1
Order By: Relevance
“…We find that ionized gas tends to contribute a small fraction of the [C ii] emission, with typical fractions around 19% in the LMC and 5% in the SMC. These contributions from ionized gas to the observed [C ii] emission are in agreement with those estimated using the unobscured [N ii] fine structure lines by Chevance et al (2016) and Okada et al (2015) in the 30 Dor and N159 regions in the LMC, respectively, and by Requena-Torres et al (2016) in several star forming regions in the SMC. The derived contributions from ionized gas to the observed [C ii] emission in the LMC and SMC are also consistent with those estimated in the Galactic plane (Pineda et al 2013).…”
Section: Ionized Gassupporting
confidence: 86%
See 1 more Smart Citation
“…We find that ionized gas tends to contribute a small fraction of the [C ii] emission, with typical fractions around 19% in the LMC and 5% in the SMC. These contributions from ionized gas to the observed [C ii] emission are in agreement with those estimated using the unobscured [N ii] fine structure lines by Chevance et al (2016) and Okada et al (2015) in the 30 Dor and N159 regions in the LMC, respectively, and by Requena-Torres et al (2016) in several star forming regions in the SMC. The derived contributions from ionized gas to the observed [C ii] emission in the LMC and SMC are also consistent with those estimated in the Galactic plane (Pineda et al 2013).…”
Section: Ionized Gassupporting
confidence: 86%
“…The 30 Doradus region in the LMC has been studied in detail with the PACS instrument on Herschel (Chevance et al 2016). High velocity resolution [C ii] images of H ii regions in the LMC and SMC are starting to become available using SOFIA (Okada et al 2015;Requena-Torres et al 2016).…”
Section: Observations Of the Distribution Of [C Ii] [C I]mentioning
confidence: 99%
“…The H i profile is always much broader than the CO and [C ii] profiles, with FWHM in the range ≈ 16 − 40 km s −1 . Similar results were found in various star-forming regions within nearby galaxies (Braine et al 2012;de Blok et al 2016;Requena-Torres et al 2016;Okada et al 2015;Fahrion et al 2017) .…”
Section: Comparison Of the Spectral Profilessupporting
confidence: 84%
“…These galaxies can have very weak CO emission (Schruba et al 2012;Cormier et al 2014). At the same time, dwarf galaxies can produce stars at rates that are normally found in starburst galaxies (e.g., Gallagher & Hunter 1984;Hunter et al 1989).…”
Section: Introductionmentioning
confidence: 96%
“…Nonetheless, the CO-to-H 2 conversion factor is a controversial quantity as it seems to vary with metallicity (Bolatto et al 2013;Poglitsch et al 1995;Cormier et al 2014;Narayanan et al 2011;Glover & Mac Low 2011). Furthermore, evidence for hidden molecular hydrogen ("CO-Dark Molecular Gas", Wolfire et al 2010) has been found not only in the Milky Way Planck Collaboration XIX 2011;Grenier et al 2005), but also in other galaxies (Israel 1997;Madden et al 1997;Requena-Torres et al 2016).…”
Section: Introductionmentioning
confidence: 99%